Infection hospitalisation in systemic lupus in Sweden - Iva Gunnarsson; Elizabeth V Arkema; Marios Rossides; Julia F Simard (Lupus Science and Medicine)
Objective Immune dysregulation in SLE and the corresponding immune-modulating and immunosuppressive nature of the treatments may play key roles in infection risk. We compared serious infection rates among individuals with incident SLE with the general population, and examined the role of treatment initiation in SLE.Methods Newly diagnosed patients with SLE (2006–2013) and general population comparators from the Swedish Lupus Linkage cohort were followed for serious infection through 2016. Adjusted Cox and frailty models estimated the relative risk of first and recurrent infections, respectively. Using a new-user design, rates of serious infections were compared between disease-modifying antirheumatic drugs (DMARDs) and hydroxychloroquine (HCQ) initiators. We then evaluated three DMARDs (azathioprine, mycophenolate mofetil and methotrexate) in multivariable-adjusted models.Results Individuals with SLE experienced more infections (22% vs 6%), especially during the first year of follow-up, and recurrent serious infections were also more common (HR=2.22, 95% CI 1.93 to 2.56). DMARDs were associated with a higher rate of serious infection versus HCQ (HR=1.82, 95% CI 1.27 to 2.60), which attenuated after multivariable-adjustment (HR=1.30, 95% CI 0.86 to 1.95). Among DMARDs, azathioprine was associated with infection (HR=2.19, 95% CI 1.14 to 4.21) and mycophenolate mofetil yielded an HR=1.39 (95% CI 0.65 to 2.96) in multivariable-adjusted models compared with methotrexate. Results were comparable across numerous sensitivity analyses.Conclusion Individuals with incident SLE were 2–4 times more likely to be hospitalised for infection and experienced more recurrent infections than the general population. Among DMARD initiators, azathioprine was associated with the highest rate.